Research on the coupled dynamics and prediction of Macao’s tourism-economy-ecosystem from a policy perspective - Xieqihua Liu; Sirui Li; Yi Zhu; Ke Song; Hok Kun Wan (PLoS ONE, 2025)
A harmonious integration of urban tourism, economy, society, and environmental development is crucial for the sustainable development of urban tourism. This study takes the Macao Special Administrative Region as a case, constructing an evaluation index system and a coordination development model for the tourism industry (TI), regional economy (RE), and ecological environment (EE). The study analyzes the coordinated development of these three systems from 2014 to 2023 and uses the GM(1,1) model to forecast the coordination development trend from 2024 to 2026. The results show that during the observation period, the comprehensive evaluation indices of the TI and EE subsystems exhibited significant growth, particularly in the EE system, which had a marked positive impact on the coupling coordination degree. The RE system, however, experienced a short-term decline due to the impact of the pandemic. Despite that, there is still considerable room for improvement in the coupling and coordination capability between Macao’s TI, RE, and EE. In recent years, the relationship between the three has shifted from an initial stage of gradual imbalance to a primary coordination stage. The forecast indicates that in the next three years, the degree of coupling coordination among Macao’s TI, RE, and EE will increase massively, with the systems becoming more synergistic. By 2026, the coordination is expected to progress from the primary to the intermediate stage. This study reveals the dynamic synergistic relationship among the TI, RE, and EE in Macao through the coupled coordination model, verifies the applicability of the coupled coordination theory in the study of sustainable development of regional tourism, and expands its research connotation in the context of coping with emergencies. At the same time, this paper puts forward three suggestions to promote the multifaceted development of the tourism industry, to promote the optimization of the structure of the regional economy and its multifaceted development, and to build an ecologically civilized city. At the same time, the paper puts forward three suggestions, expecting to provide more in-depth theoretical support and practical guidance for the sustainable development of Macau and other tourist cities.